Micropapillary Variant of Urothelial Carcinoma - Ghee Young Kwon (Advances in Urology, 2011)
Micropapillary carcinoma (MPC) of urinary tract is an uncommon variant of urothelial carcinoma with significant diagnostic and prognostic implications. Though MPC shows characteristic microscopic features, there exists interobserver variability and also it needs to be differentiated from the metastasis from other organs. The prognosis is generally poor, depending on the proportion of the micropapillary component in some reports. Early cystectomy in cases with only lamina propria invasion may be indicated according to recent studies. This review outlines the general features of this entity and briefly comments on the controversies and the recent development.